The influence of industrial attitudes and behaviours in adopting sustainable construction practices. (1st November 2022) - Maqbool, Rashid; Saiba, Mohammed Rayan; Altuwaim, Ayman; Rashid, Yahya; Ashfaq, Saleha
Abstract: Considering the rapid environmental changes, the transitions to sustainable practices in the construction industry is vital now. Though the developed construction industries have already made efforts to switching to more sustainable and environment friendly practices, the developing countries are still lacking it. This research was organised to understand the role of project management practises and integrated methods in the sustainable development in the developing countries, for looking on how such practices can help these construction sectors become sustainable. The moderation effect of industrial attitudes and behaviours on sustainable construction was also conducted to understand the intermediary impacts. A survey based on the snowball sample of 208 construction professionals in Ghana was conducted to determine the impact of project management practises and integrated methods on sustainable construction. Research model was tested by employing bivariate correlation and multiple hierarchical regression analysis techniques, to establish the interrelationships among the project management practices, integrated approaches, industrial attitudes and behaviours, and sustainable construction and to explain these constructs in terms of their common underlying dimensions. The findings highlight that the project management practices and integrated approaches are significantly impacting on the sustainable construction practices in terms of BIM, Digital Twin, LEED, and BREEAM. Whereas the industrial attitudes and behaviours were found to be affecting the project management practises and integrated approaches through moderating role on sustainable construction. The study was concluded by suggesting the importance of sustainable construction practices and shaping industrial attitudes and behaviours towards such practices in the developing construction industries.